PERANAN PENGURUS KELOMPOK BELAJAR PROGRAM PENDIDIKAN DASAR DALAM PENYELENGGARAAN LAYANAN SISTEM BELAJAR JARAK JAUH DI UPBJJ-UT SERANG - Saleha, Eha (LPPM Universitas Terbuka, 2019)
Group administrators Learning Pendas’s students is an important part of the system for implementing distance learning services in each Open University Distance Learning Program Unit. However, the description and research related to the role of the board of education officers is still very limited. To achieve this, descriptive qualitative research has been carried out with participatory action research (PAR) strategies for all PGSD and PG-PAUD student management and service activities carried out by pokar administrators throughout the Banten region under the auspices of UPBJJ-UT Serang. The results of the study showed that the administrators of the pendas program had a role in the implementation of distance learning system services at UT Serang UPBJJ especially in promotional activities, new student recruitment, New Student Study Orientation, distribution of teaching materials, PKP / PKM tutorials and compulsory and examination and Diploma Submission Ceremony (UPI).